Tinjauan Yuridis Sosiologis Terhadap Tindak Pidana Perjudian di Kabupaten Bulukumba - Sari, Eka Anugra; Hamsir (Alauddin Law Development Journal, 2023)
This research analyzes the application of criminal law to gambling offenses and the efforts of law enforcement in combating gambling in Bulukumba. Using normative and empirical juridical approaches, the study finds that environmental factors, hobbies, unemployment, and the desire for quick financial gain contribute to the prevalence of gambling. Article 303 of the Criminal Code threatens imprisonment of up to 10 years or a fine of 25 million Indonesian Rupiah for those who facilitate gambling, and imprisonment of up to 4 years and a fine of 10 million Indonesian Rupiah for gambling participants. The Law No. 7 of 1974 also declares gambling as a criminal offense. This research highlights the importance of law enforcement efforts in preventing and prosecuting gambling offenses.